2008
DOI: 10.1136/bjsm.2008.046227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded bicycle seat pressure on perineal compression: a magnetic resonance imaging analysis: Figure 1

Abstract: Substantial compression of the perineal cavernous spaces may occur with total seat pressure values of less than 40% of typical seat loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recent data presented by Bressel and Nuckles [33] reported similar perineal pressures (22.7 kPa) in cyclists using a traditional racing saddle. That study indicated that the perineal pressure must be reduced by 60% (to approximately 7 kPa) to remove compression to the corpus spongiosum and corpora cavernosa of the cyclist measured using MRI.…”
Section: Discussionmentioning
confidence: 67%
“…Recent data presented by Bressel and Nuckles [33] reported similar perineal pressures (22.7 kPa) in cyclists using a traditional racing saddle. That study indicated that the perineal pressure must be reduced by 60% (to approximately 7 kPa) to remove compression to the corpus spongiosum and corpora cavernosa of the cyclist measured using MRI.…”
Section: Discussionmentioning
confidence: 67%
“… Bressel & Parker, (2010) observed that a 60% reduction of typical seated pressure resulted in reduced perineal compression. Lowe, Schrader & Breitenstein (2004) showed that the “no-nose” saddles resulted in reduction of pressure in the anterior region by more than 40% in a stationary trial setting.…”
Section: Discussionmentioning
confidence: 99%
“…At least a 60% reduction of anterior seat pressure is necessary to significantly decrease internal perineal compression [40]. Using the no-nose saddle resulted in a 71% reduction, which was associated with an increase of penile oxygen pressure, reduction of the discomfort in the perineum, and a smaller incidence of perineal numbness.…”
Section: Different Types Of Saddlementioning
confidence: 99%